Tunable NaBH4 Nanostructures Revealing Structure‐Dependent Hydrogen Release. Issue 9 (7th September 2021) - Salman, Muhammad Saad; Rawal, Aditya; Aguey-Zinsou, Kondo-Francois
Abstract : Hydrogen evolution or generation In article number 2100063, Kondo‐Francois Aguey‐Zinsou and co‐workers design NaBH4 as spheres, cubes and bars of varying sizes using surfactants. The deliberately tuned NaBH4 nanostructures reveal structure dependent hydrogen release—a step forward to decipher structure‐property relationships in borohydrides for hydrogen storage and generation applications.